Inventory analysis of carbon footprint on greenhouse gas emission of large-scale biogas plants - Yuguang, Zhou; Zongxi, Zhang; Yixiang, Zhang; Jie, Zhou; Li, Chen; Xuefeng, Yin; Renjie, Dong (International Journal of Agricultural and Biological Engineering, 2016)
Inventory analysis of greenhouse gas emission for large-scale biogas plants using carbon footprint method still needs to be improved. Based on the life cycle theory, the application of carbon footprint on four large-scale biogas plants was analyzed in this paper, which comprehensively considered project progresses of civil engineering construction, operation and comprehensive utilization of residues and slurry. Also the greenhouse gas emissions during the construction and waste removal stages were analyzed and estimated. The carbon footprint of those plants was analyzed in different types and scales. The results showed that the larger scale plant will produce relatively lower carbon footprint. The greenhouse gas emission of energy production, utilization during the period of anaerobic digestion accounted for more than 96% of the entire life cycle emission. The proportion of greenhouse gas emissions on equipment, demolition recycling and transportation phases was smaller, which was less than 1.5% and should be simplified in calculation. The greenhouse gas emission of building materials production can be ignored. Keywords: biogas plant, carbon footprint, life cycle, greenhouse gas, emission reduction DOI: 10.3965/j.ijabe.20160904.2076 Citation: Zhou Y G, Zhang Z X, Zhang Y X, Zhou J, Chen L, Yin X F, et al. Inventory analysis of carbon footprint on greenhouse gas emission of large-scale biogas plants. Int J Agric & Biol Eng, 2016; 9(4): 99－105.